Counternarratives for Racial Justice: Confronting Institutionalized Racism in Higher Education - Dianne Ramdeholl; Jaye Jones (Adult Education Research Conference, 2022)
This research highlights findings from a recently published book documenting the lived experiences and struggles of racialized faculty at predominantly white institutions (PWI) within North America.
Keywords: Critical Race Theory; Adult Education; Racism; Social Justice